Host Country Policy Responses to Pull and Push Forces of Cross-border Investment. A Case Study of Foreign Direct Investment from Singapore into Malaysia in Manufacturing and Services Industry - Teh, Su Hon (2010)
Foreign Direct Investment (FDI) is generally viewed as an important national instrument to attract stable foreign capital and to enable knowledge and technology transfer. Most countries adopt a policy mix to restrict and encourage FDI in accordance to their national interest and strategy. However, more and more countries are getting open toward foreign investment in the domestic environment. The attractiveness of a FDI location is enhanced by the pull and push forces in both the host and home countries. It is therefore critical for the policy makers to identify a set of pull and push factors that might improve competitiveness of a country as a location of foreign investment. Recognising these forces, host countries may adopt various FDI related policies to retain existing and entice potential foreign direct investors. The main aim of this management project is to identify host country national policy responses to the pull and push forces that influence the flow of foreign direct investment. A case study of the cross border investment from Singapore based multinational enterprises into Malaysia in manufacturing and services industry is examined.